The Role of Australian Mosquito Species in the Transmission of Endemic and Exotic West Nile Virus Strains - Jansen, Cassie C. (MDPI, 2013)
Recent epidemic activity and its introduction into the Western Hemisphere have drawn attention to West Nile virus (WNV) as an international public health problem. Of particular concern has been the ability for the virus to cause outbreaks of disease in highly populated urban centers. Incrimination of Australian mosquito species is an essential component in determining the receptivity of Australia to the introduction and/or establishment of an exotic strain of WNV and can guide potential management strategies. Based on vector competence experiments and ecological studies, we suggest candidate Australian mosquito species that would most likely be involved in urban transmission of WNV, along with consideration of the endemic WNV subtype, Kunjin. We then examine the interaction of entomological factors with virological and vertebrate host factors, as well as likely mode of introduction, which may influence the potential for exotic WNV to become established and be maintained in urban transmission cycles in Australia.